Analysis Of Comparative Cost Efficiency Of Conventional And Semi System Formwork Methods In Wall Buildings (Case Study: Bank Indonesia Gresik Area Project): Analisis Perbandingan Efisiensi Biaya Bekisting Metode Konvensional Dan Semi Sistem Pada Bangunan Dinding (Studi Kasus: Proyek Kawasan Bank Indonesia Gresik) - JENNY SEPTYA DAMAI NAVIDA; Maulidya Octaviani B, ST.,M.MT; Wisnu Abiarto N, ST., M.MT (Universitas Negeri Surabaya, 2025)
The Bank Indonesia Gresik project, especially in the Khazanah area, has high formwork requirements for the wall elements. Payment to subcontractors is made without down payment and using a 45-day term system after invoice and work progress. The purpose of this study is to compare the cost and time efficiency between conventional and semi-system formwork methods. The research method used is the comparative method, with cost and time analysis on 11,736.48 m² of wall work. Conventional formwork uses materials such as plywood and meranti wood, while the semi-system method uses hollow and phenolic frames. The results showed that the cost of the conventional method was IDR 2,438,396,000, while the semi-system method was only IDR 1,425,760,695. In terms of time, the conventional method takes 187 days, while the semi-system method only takes 131 days. The semi-system method provides time efficiency of 29.95% and cost efficiency of up to 41.53%. In conclusion, the semi-system formwork method is more efficient in terms of cost and time than the conventional method, so it is more feasible to apply to the wall formwork work of the Bank Indonesia Gresik Area Project.